2012
DOI: 10.1590/s0102-695x2012005000046
|View full text |Cite
|
Sign up to set email alerts
|

Allicin, a SUR2 opener: possible mechanism for the treatment of diabetic hypertension in rats

Abstract: Abstract:The garlic (Allium sativum L., Amaryllidaceae) has been popularly used in the treatment of diabetes and cardiac complications. In the present work, we have studied the possible mechanisms, sulfonylurea receptor (SUR) selectivity of allicin in diabetic hypertensive rats. Diabetic hypertension was induced by intraperitoneal injection of streptozotocin (50 mg/kg) followed by daily administration of dexamethasone (10 μg/kg, s.c.). Different parameters, blood pressure and blood glucose levels were studied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 37 publications
0
6
0
2
Order By: Relevance
“… 5 , 6 , 11 , 30 , 31 This report was further supported by the finding that allicin selectively opens SUR2, a type of K + channel receptor, present in blood vessels, leading to dilation of blood vessels, which may be a possible mechanism for the antihypertensive activity of allicin. 32 Other studies have also revealed that fresh garlic extract (allicin) has inhibitory activity against angiotensin 1 converting enzyme and diuretic activity, which may be involved in the antihypertensive action of garlic. 10 , 11 , 12 , 28 , 33 , 34 …”
Section: Discussionmentioning
confidence: 99%
“… 5 , 6 , 11 , 30 , 31 This report was further supported by the finding that allicin selectively opens SUR2, a type of K + channel receptor, present in blood vessels, leading to dilation of blood vessels, which may be a possible mechanism for the antihypertensive activity of allicin. 32 Other studies have also revealed that fresh garlic extract (allicin) has inhibitory activity against angiotensin 1 converting enzyme and diuretic activity, which may be involved in the antihypertensive action of garlic. 10 , 11 , 12 , 28 , 33 , 34 …”
Section: Discussionmentioning
confidence: 99%
“…Sin embargo, actualmente hay varios estudios que continúan utilizando la alicina en distintos grados de pureza y es probable que por ello aún exista controversia respecto a cuál es la dosis o concentración óptima de la alicina capaz de inducir efectos benéficos. A este respecto, la dosis de la alicina reportada para obtener efectos cardioprotectores en modelos experimentales es a dosis tan bajas como 8 mg/kg 44 . En pacientes, las dosis utilizadas para obtener un efecto terapéutico está en un rango más amplio, el cual va de los 10 a los 40 mg/día y no se han documentado o descrito efectos adversos, ni mal olor, tanto en estudios a corto como a largo plazo 24,25,45 .…”
Section: Discussionunclassified
“…Mediante el análisis in silico se concluyó que la alicina actúa en forma similar al losartán (antihipertensivo antagonista del AT1R) 43 . En ratas diabéticas hipertensas, la alicina redujo la hipertensión por un mecanismo que implicó la apertura de un canal de potasio dependiente de trifosfato de adenosina y la participación del receptor de sulfonilurea tipo 2 44 . En pacientes con hipertensión severa, la alicina demostró un efecto antihipertensivo 5 horas después de la administración y con una duración máxima de 5-14 horas 45 .…”
Section: Hipertensión Arterialunclassified
“…In this respect, allicin induces antihypertensive effects in vivo in hypertensive rats, while in vitro showed concentration-dependent and endothelium-dependent vasorelaxant effects in vascular smooth muscle cells, such effects were mediated by the production of H 2 S. Allicin increased the levels of cyclic guanosine monophosphate (cGMP), cyclic adenosine monophosphate (cAMP), and endothelium-derived hyperpolarizing factor (EDHF)-mediated relaxation [ 87 ]. In hypertensive diabetic rats, allicin reduced hyperglycemia and hypertension by a mechanism related to the opening of an ATP-dependent potassium channel (K ATP channel) with the participation of the type 2 sulfonylurea receptor (SUR2) [ 88 ]. On the other hand, in experimental CKD, allicin reduced hypertension, oxidative stress, and improved renal function.…”
Section: Effects Of Allicin On Cardiovascular Risk Factorsmentioning
confidence: 99%